Developing self-regulatory framework in a Malaysian media environment. - Abdullah, Zulhamri; Hassan, Md Salleh; AlSagoff, Syed Agil (2012)
An increasingly demand of digital media and information communication technology in a borderless world has encouraged Malaysia to move to a new era of knowledge creation and fast-moving competitive advantages especially in a media sector. The phenomenon has blurred the boundaries between broadcasting and computing industries in terms their roles, functions, and economic scales. This new technological environment in Malaysia has resulted in conflicts and challenges to the country. It may affect the current regulatory media approach and technology acceptance in harmonizing the digital intellectual property, market power, content values, and diversion of cultures. The purpose of this paper is to identify the mechanism, concepts, and implementation of self-regulation of Malaysian media environment. The primary regulatory reference of the study is the Communication Act 1998. The media industry players in this study are the media organizations that are governed by the Communication and Multimedia Act 1998 and the members of Communication and Multimedia Content Forum (CMCF). The focus on the self-regulation and its procedures is based on the Content Code developed by the Content Forum of the media Industry. This study provides a useful insight of analyzing the development of Malaysia legislations and cyber policies and the implementation and practices among the Malaysian media players. This study shed information on the relevance and usefulness of local legislations and policies to the local media practitioners and industry.